Implementation of Curriculum Management in Educational Institutions - Nur Aisyah Rohmawati (Jurnal Pendidikan Nusantara, 2023)
This article is to assess and comprehend Madrasah Ibtidaiyah Ponorogo Islamic Center's execution of Islamic education program management. This study combines a descriptive analytic method with a qualitative article approach. Descriptive analysis was used for data gathering, with a focus on the administration of Islamic education programs and the elements that help or impede their implementation. At the Madrasah Ibtidaiyah Ponorogo Islamic Center, a variety of relevant parties, including instructors, students, and parents, participated in the article. The article results show that Madrasah Ibtidaiyah Islamic Center Ponorogo has a unique approach in implementing curriculum management. The integration of Islamic values, ethical education, and a holistic approach are characteristic of the learning process. Supporting factors for implementing curriculum management include awareness of the importance of ethical education as a foundation, integration of Al-Qur'an values in every aspect of life, and various extracurricular programs outside of school. On the other hand, obstacles arise in rapid adaptation to curriculum changes and lack of coordination with participants from the Ministries of Religious Affairs and Education. This article provides an in-depth picture of how Islamic education curriculum management at the MI Islamic Center Ponorogo can create a holistic learning environment based on Islamic values. These results can aid in the development of tactics and guidelines for Islamic education, especially at the elementary level, in order to increase its effectiveness and relevance to the demands of the times